Inflammatory Myopathy Causing Leg Pain in a Soccer Player: Case Report and Return‐to‐Play Considerations. Issue 4 (28th September 2015) - Lueders, Daniel R.; Howe, Benjamin M.; Sellon, Jacob L.
Abstract: Leg pain is a common condition in athletes as well as in the general population, and has a broad differential diagnosis that includes musculoskeletal, vascular, rheumatologic, and neurologic etiologies. Idiopathic inflammatory myopathy (IM) is a relatively uncommon but recognized etiology of leg pain. In this case, we describe an acute presentation of IM in an athlete resulting in leg pain and activity limitation. The available literature suggests that moderate‐intensity exercise is safe and beneficial in idiopathic IM, but studies to date have not assessed the effects of high‐intensity exercise in IM or provided recommendations for return to competitive contact sport in this population.